2016
DOI: 10.1080/19490976.2016.1218585
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome, the microbiota and the gut-brain axis

Abstract: Irritable bowel syndrome is a common functional gastrointestinal disorder and it is now evident that irritable bowel syndrome is a multi-factorial complex of changes in microbiota and immunology. The bidirectional neurohumoral integrated communication between the microbiota and the autonomous nervous system is called the gut-brain-axis, which integrates brain and GI functions, such as gut motility, appetite and weight. The gut-brain-axis has a central function in the perpetuation of irritable bowel syndrome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
159
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(173 citation statements)
references
References 165 publications
2
159
0
12
Order By: Relevance
“…However, data on the differences in the abundance of specific species within these two microbial phyla between IBS and HC are not consistent . In addition, a few recent clinical studies have demonstrated that compositional changes in the intestinal microbiota in IBS are associated with relevant abnormal gastrointestinal and brain–gut axis functions that are often observed in patients with IBS . Taken together, these findings suggest that the gut microbiome plays a role in IBS.…”
Section: Introductionmentioning
confidence: 92%
“…However, data on the differences in the abundance of specific species within these two microbial phyla between IBS and HC are not consistent . In addition, a few recent clinical studies have demonstrated that compositional changes in the intestinal microbiota in IBS are associated with relevant abnormal gastrointestinal and brain–gut axis functions that are often observed in patients with IBS . Taken together, these findings suggest that the gut microbiome plays a role in IBS.…”
Section: Introductionmentioning
confidence: 92%
“…A population density above a threshold level is required for probiotic efficacy in the human gut and skin. Indeed, disease symptoms in the gut, such as irritable bowel disease, or on the skin, are correlated with a lack of certain microbial colonizers and effective levels of others (Raskov et al, 2016;Winter and Baumler, 2014). The formation of biofilms of probiotics is important for their functioning in the gut.…”
Section: Probiotic Trait: the Significance Of Biofilm Formation By Thmentioning
confidence: 99%
“…Examples of the role of microbiota imbalances are reductions in Lactobacillus and Bacteroidetes spp., and increases in Streptococcus spp. (34). An increase in the Firmicutes/ Bacteroides ratio was found in a subgroup of IBS patients (16), and reduced bacterial diversity was observed in other IBS patients (34).…”
Section: Microbiota and Post-infectious Irritable Bowel Syndromementioning
confidence: 93%
“…Both qualitative and quantitative variations of the microbiota (31) may play a role in initiating and perpetuating IBS signs in many patients (34). Examples of the role of microbiota imbalances are reductions in Lactobacillus and Bacteroidetes spp., and increases in Streptococcus spp.…”
Section: Microbiota and Post-infectious Irritable Bowel Syndromementioning
confidence: 99%